Intuitiveness 3D objects Interaction in Augmented Reality Using S-PI Algorithm - Ajune Wanis Ismail; Mohd Shahrizal Sunar (Institute of Advanced Engineering and Science, 2013)
Numbers of researchers have developed interaction techniques in Augmented Reality (AR) application. Some of them proposed new technique for user interaction with different types of interfaces which could bring great promise for intuitive user interaction with 3D data naturally. This paper will explore the 3D object manipulation performs in single-point interaction (S-PI) technique in AR environment. The new interaction algorithm, S-PI technique, is point-based intersection designed to detect the interaction’s behaviors such as translate, rotate, clone and for intuitive 3D object handling. The S-PI technique is proposed with marker-based tracking in order to improve the trade-off between the accuracy and speed in manipulating 3D object in real-time. The method is robust required to ensure both elements of real and virtual can be combined relative to the user’s viewpoints and reduce system lag. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2797